Addressing Perceived Skill Deficiencies in Student Affairs Graduate Preparation Programs. Issue 2 (2nd April 2016) - Cooper, Jay; Mitchell, Donald; Eckerle, Kayle; Martin, Kyle
Abstract : This article explores existing literature on perceived skill deficiencies among entry-level student affairs practitioners. Through a review of recent literature, seven perceived skill deficiencies were identified, including budgeting and financial management, strategic planning, research and assessment, legal knowledge and standards, supervision, technological competence, and institutional and campus politics. Content analysis of graduate preparation program websites was used to determine the degree to which each of these deficiencies are purported to be addressed.